Remediation of ozone pollution by ornamental plants in indoor environment - P. Saxena; S. Sonwani (Global Journal of Environmental Science and Management)
The indoor air quality is much more matter of concern as relative to ambient or outdoor air quality, especially in the context of human health.  However, very few studies have been reported for remediation of indoor ozone by plant species. The main objective of this study is to evaluate ozone deposition velocities and ozone removal effectiveness of three indoor ornamental plant species (Dracaena deremensis, Tagetes erecta and Lilium candidum) that can be used in the remediation of indoor ozone. Ozone deposition velocity was estimated through measurement of leaf surface areas of selected plant species and exposing them to 3-regular daytime cycles where ozone concentrations under controlled conditions first increased from 8 h followed by 16 h in the absence of ozone. Values of ozone deposition velocity after the completion of first exposure were found maximum (7.7 m/h) in case of Dracaena deremensis and minimum (0.5 m/h) after the completion third exposure in Lilium candidum. The ozone removal effectiveness found in the range of 0.7 to 13% for leaf surface area to room volume ratio of 0.06/m with reference to an air exchange system and background loss present in an indoor environment. Among the selected plant species, Dracaena deremensis has got the highest ozone deposition velocity as well as ozone removal effectiveness and Lilium candidum has got the lowest values. Hence, this study concludes with the sustainable use of ornamental plant species in the remediation of the indoor ozone pollution, which can further help in improving the health condition of the residents.